Identifying potential biomarkers related to pre-term delivery by proteomic analysis of amniotic fluid - Hong, Subeen; Lee, Ji Eun; Kim, Yu Mi; Park, Yehyon; Choi, Ji-Woong; Park, Kyo Hoon (Nature Publishing Group, 2020)
We sought to identify biomarkers in the amniotic fluid (AF) and specific signaling pathways related to spontaneous preterm delivery (SPTD, <34 weeks) in women with preterm labor (PTL) without intra-uterine infection/inflammation (IUI). This was a retrospective cohort study of a total of 139 PTL women with singleton gestation (24+0 to 32+6 weeks) who underwent amniocentesis and who displayed no evidence of IUI. A nested case-control was conducted using pooled AF samples (n=20) analyzed via label-free liquid chromatography-tandem mass spectrometry. In the total cohort, an ELISA validation study was performed for seven candidate proteins of interest. Proteomic analysis identified 77 differentially expressed proteins (DEPs, P<0.05) in the AF from SPTD cases compared to term delivery controls. ELISA validation confirmed that women who had an SPTD before 34 weeks had significantly independently lower levels of VEGFR-1 and higher levels of lipocalin-2 and the Fc fragment of IgG binding protein in the AF. Five principle pathways associated with the 77 DEPs were identified, including glycolysis, gluconeogenesis, and iron homeostasis. The proteomic analysis data of AFs from women with PTL identified several novel biomarkers and specific protein pathways related to SPTD in the absence of IUI.